Experimental study of phase equilibria in the Al2O3–MgO–TiO2 system and thermodynamic assessment of the binary MgO–TiO2 system. Issue 11 (23rd May 2018) - Ilatovskaia, Mariia; Saenko, Ivan; Savinykh, Galina; Fabrichnaya, Olga
Abstract: Phase relations in the MgO–TiO2 and Al2 O3 –MgO–TiO2 systems have been studied experimentally using X‐ray diffraction, scanning electron microscopy combined with dispersive X‐ray spectrometry, and differential thermal analysis. The heat capacity measurements of the Mg2 TiO4, MgTiO3, and MgTi2 O5 compounds have been carried out in the temperature range of 473‐1373 K using DSC. A new thermodynamic description of the MgO–TiO2 system has been derived based on obtained experimental results, data from literature, and taking into account the cation disordering of the intermediate compounds Mg2 TiO4 and MgTi2 O5 . The liquid phase was described by the two‐sublattice partially ionic model (Mg +2, Ti +2, Ti +3 )(O −2, Va, O, TiO2 ). For the Al2 O3 –MgO–TiO2 system: the solid‐state invariant reaction involving the intermediate phase of pseudobrookite solid solution have been found at the temperature of 1433 K. On the liquidus surface, the eutectic invariant reaction has been established at 1843 K and the transitional one—at 2006 K. Based on the obtained experimental results isothermal sections within the range 1269‐1697 K of the ternary system have been predicted. The MgTi2 O5 –Al2 TiO5 section has been constructed.